Hubungan antara Bersepeda dan Infertilitas Pria: Tinjauan Sistematis dari Penelitian Saat Ini: Analisis - Kemal Akbar Suryoadji; Alifaturrasyid Syafaatullah Ridwan; Ahmad Fauzi; Kieran Pasha Ivan Sini; Akmal Taher (PT Kalbe Farma Tbk., 2025)
Introduction: Cycling is a popular sport and also has various health benefits. However, cycling carries health risks, including fertility problems. This research aims to explore the association between cycling and infertility in men. Methods: This systematic review was conducted according to a PROSPERO protocol (ID: CRD42024509255) and PRISMA guidelines using the PubMed, Cochrane, and ScienceDirect databases. Keywords “(Bicycle) AND (Infertility)” are used. The risk of bias was assessed based on the Cochrane risk of bias tool for cohort studies. Results: The final two cohort studies were included with a total of 487 cyclists. Regular cycling of more than 1.5 hours/week was associated with 34% (95% CI 4-55%) lower sperm concentration compared to control. Regular cycling of more than 5 hours/week was associated with lower sperm concentration (OR 1.92, 95% CI 1.03-3.56) and lower total sperm motility (OR 2.05, 95% CI 1.19-3.56) compared to the control group. Conclusion: There is a relationship between cycling and male infertility; a decrease in sperm concentration in men who cycle at least 1.5 hours/week and lower sperm motility in men who cycle for at least 5 hours/week. The direct efect of cycling on the incidence of infertility as a consequence needs to be explored further.